Terrorism in two novelistic appropriations of Hamlet - Mohammad Safaei, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Shakespeare’s Hamlet, as a revenge tragedy, demonstrates an ambience of terror. This ambience emerges in two works which have appropriated the play: The Story of Edgar Sawtelle by David Wroblewski (2009) and The Dead Fathers Club by Matt Haig (2006). However, the present article tends to presume the contemporary history, i.e. post 9/11 era, as the basis for investigating a variety of themes and relations between Hamlet and its two novelistic appropriations. Drawing upon the work of experts in terrorism psychology, I explore the psychological commonalities of the modern Hamlets, who can be distinguished by their isolation, vulnerability, and self-delusion. Attempts are also made to investigate the psychological bases for the juxtaposition of the specters in the two novels with the terrorist leadership in today’s world. Appropriative literature is often denigrated for its lack of originality and being indebted to its canonical sources; such a reductionist assumption stems from our conception of appropriative literature as the recycling of previous literary works. This paper attempts to demonstrate that the two novels are not to be readily categorized as cultural or artistic reuse of Hamlet. In the same way that Hamlet reveals the political tensions of Elizabethan reign, its two modern appropriations can arguably reflect the social and psychological symptoms of terrorism in our era.